Sales Volume Improvement From Marketing Communication Skills Perspective - Mutiara Sholihah, Alvina; Eda, Eda; Muntiarsih, Tiara (International Journal of Business, Law, and Education, 2024)
The purpose of this study is to determine the effect of marketing communication skills on increasing insurance sales volume of PT Axa Mandiri Financially Service. Marketing communication skills are proxied with 3 free indicators, namely knowledge, skills, motivation. The type of research used in this study is quantitative research. The sampling technique used is purposive sampling with a sample of 50 respondents. This study is an associative study. The data used in this study were obtained using research instruments, namely questionnaires, then analysis through validity tests, reality tests, classical assumption tests, regression analysis, coefficients of determination, and tests between knowledge variables (X₁), skills (X₂), and motivation (X3). Partially, the variables of knowledge (X₁), skill (X₂), and motivation (X3) have a positive effect on increasing insurance sales volume at PT Axa Mandiri Financially Service.